The digitalisation of roadmapping workshops - Gouvêa de Oliveira, Maicon; Routley, Michèle; Phaal, Robert (Elsevier, 2022)
Roadmapping lacks development regarding the application of digital tools. Although roadmapping software is analysed in the literature, it does not address the people-centric characteristics required in workshops. This paper investigates the digitalisation of roadmapping workshops using a psychosocial framework (cogitate, articulate, and communicate). Three research phases were conducted to analyse workshops that replaced physical tools (paper charts, sticky notes, and stickers) with digital tools (interactive display, personal computer, and whiteboard software). The results of this study show that the digital tools used can support co-located roadmapping activities, delivering potential improvements, particularly for creating strategic narratives in the articulate stage.
Keywords: Roadmapping; Workshop; Digitalisation; Digital; Software; Whiteboard; Sticky-note; Interactive display